PERAN PENDIDIKAN DALAM PROSES PEMBUDAYAAN SEBAGAI TRANSFORMASI BUDAYA PADA ERA MILINEAL - Yusda Novianti (Jurnal Sintaksis, 2022)
This research is motivated by the lightning phenomenon and the enormity of the change of life in the globalization era with advances in data and communication technology. This information age became the forerunner to the birth of the millennial generation and generation; a generation that makes data and its devices an integral part of their lives. This research aims to describe the reality of human life in the global era with all its achievements in the form of openness and ease of interaction and communication and various facilities. With the civilizing process, a reflection is obtained that this information age focuses on the era of system uniformity and the value of human life with a single universal cultural spirit. Efforts to transform culture in this global context demand a transformative position in the world of learning in its various aspects. Cultural transformation to students can be done with a transformative epistemological paradigm. Various literature studies used in this research take the form of: various reference books, journal articles, and various other academic manuscripts.